Activation of Peptidylarginine Deiminase in the Salivary Glands of Balb/c Mice Drives the Citrullination of Ro and La Ribonucleoproteins. (26th November 2017) - Rodríguez-Rodríguez, Mayra; Herrera-Esparza, Rafael; Bollain y Goytia, Juan-José; Pérez-Pérez, María-Elena; Pacheco-Tovar, Deyanira; Murillo-Vázquez, Jessica; Pacheco-Tovar, Guadalupe; Avalos-Díaz, Esperanza
Abstract : The goal of the present study was to determine whether peptidylarginine deiminase PAD2 and PAD4 enzymes are present in Balb/c mouse salivary glands and whether they are able to citrullinate Ro and La ribonucleoproteins. Salivary glands from Balb/c mice were cultured in DMEM and supplemented with one of the following stimulants: ATP, LPS, TNF, IFN γ, or IL-6. A control group without stimulant was also evaluated. PAD2, PAD4, citrullinated peptides, Ro60, and La were detected by immunohistochemistry and double immunofluorescence. PAD2 and PAD4 mRNAs and protein expression were detected by qPCR and Western blot analysis. PAD activity was assessed using an antigen capture enzyme-linked immunosorbent assay. LPS, ATP, and TNF triggered PAD2 and PAD4 expression; in contrast, no expression was detected in the control group (p < 0.001 ). PAD transcription slightly increased in response to stimulation. Additionally, PAD2/4 activity modified the arginine residues of a reporter protein (fibrinogen) in vitro . PADs citrullinated Ro60 and La ribonucleoproteins in vivo . Molecular stimulants induced apoptosis in ductal cells and the externalization of Ro60 and La ribonucleoproteins onto apoptotic membranes. PAD enzymes citrullinate Ro and La ribonucleoproteins, and this experimental approach may facilitate our understanding of the role of posttranslational modifications in the pathophysiology of Sjögren's syndrome.